(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Vitamin E has been used as antioxidant and in the treatment of various ailments due to oxidative stress. The cardio-protective effect of vitamin E in dexamethasone induced oxidative stress was studied. Forty Wistar rats were randomly assigned to four groups of 10 rats each. Control group received normal rat chow. Oxidative stress was induced using 30µg/kg body weight of dexamethasone (DEX) intraperitonealy in DEX+Vit E and DEX only groups while Vitamin E was administered orally at a dose of 300 IU/kg to Vitamin E only group and DEX+Vit E group daily for 14 days. All animals were fed ad libitum and had free access to water. Blood samples were obtained by cardiac puncture for biochemical analyses while heart and kidney were processed for histological staining. The result shows a significant (p<0.05) decrease in serum nitric oxide, bilirubin and superoxide dismutase concentration in DEX-only group which was elevated following vitamin E treatment. The angiotensin converting enzyme and lactate dehydrogenase enzyme activities were significantly (p<0.01) elevated in DEX-only group compared with control and DEX+Vit E groups. These enzyme levels were significantly (p<0.01) reduced in DEX + vitamin E group. The histology of the heart and the kidney in DEX-only group showed cardiac hypertrophy and kidney injury but were ameliorated by vitamin E treatment. The results suggest that vitamin E has cardiac and renal protective effect and ameliorates oxidative injury to the heart and kidney due to oxidative stress.